Tinjauan Pengaruh Desain Ruang terhadap Perilaku Belajar Mahasiswa: Studi Kasus Studio B Arsitektur USK - Ulfa Mazaya; Karima Adilla; Cut Fatin Najla; Fathin 'Afifah; Mau'idhah Hasanah; Nafila Rizki Fadhil; Muhammad Adil Rizqillah; Muhammad Rayyan Adlya (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
This study explores how the design elements of Studio B at the Department of Architecture and Planning, Syiah Kuala University, influence students' learning behavior. Usinga descriptive qualitative approach, data were collected through observation and questionnaires. Observational findings revealed that physical elements such as lighting, ventilation, and furniture arrangement play a significant role in creating a comfortable learning environment. Questionnaire results indicated that most respondents felt moderately to highly comfortable with aspects such as lighting, air circulation, and ventilation, which positively impacted their productivity.